Community-Based Water Law and Water Resource Management Reform in Developing Countries 2007
DOI: 10.1079/9781845933265.0211
|View full text |Cite
|
Sign up to set email alerts
|

If government failed, how are we to succeed? The importance of history and context in present-day irrigation reform in Malawi.

Abstract: This chapter examines the interface between new, formal irrigation, water policies and laws and long-standing customary practices in two smallholder irrigation schemes earmarked for transfer to water user associations in Malawi. It documents how local histories and practices are shaping access to critical land and water resources in ways not anticipated by technocratic irrigation and water reform implementers. At this point, rather than creating a climate encouraging more equitable economic growth by making sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Others sketch similar situations in different countries. For example, Ferguson and Mulwafu (2007) reported that the top-down enforcement of WUAs weakened smallholder farmer participation in Malawi. Also, in Kenya, Kemerink et al (2016Kemerink et al ( : 1072 found that WUA members cannot participate meaningfully due to "predetermined and biased organization structures introduced by the policy" despite the established legal basis for WUA formation.…”
Section: Governancementioning
confidence: 99%
See 3 more Smart Citations
“…Others sketch similar situations in different countries. For example, Ferguson and Mulwafu (2007) reported that the top-down enforcement of WUAs weakened smallholder farmer participation in Malawi. Also, in Kenya, Kemerink et al (2016Kemerink et al ( : 1072 found that WUA members cannot participate meaningfully due to "predetermined and biased organization structures introduced by the policy" despite the established legal basis for WUA formation.…”
Section: Governancementioning
confidence: 99%
“…Leadership positions are often assumed by local elites through various means (Ferguson and Mulwafu 2007;Kemerink et al 2016;Sokile and van Koppen 2004), even when they have technically been 'elected' by all WUA members (Zuka 2016). In this position, local elites benefit most "from new opportunities provided by the irrigation reform in terms of training, access to information and abilities to shape the rules governing scheme functioning" (Ferguson and Mulwafu 2007: 224).…”
Section: Governancementioning
confidence: 99%
See 2 more Smart Citations
“…But livelihood strategies in rural Malawi are much more complex than this and, importantly, involve the complex interplay of farming both inside and outside of irrigation schemes with farmers having access to both sorts of land (Ferguson and Mulwafu 2007). It is unlikely ever to be the case that farmers are full time irrigators.…”
Section: Irrigated and Non-irrigated Farmingmentioning
confidence: 99%